The Problem Based Learning Model with Etnomatematics Nuance by Using Traditional Games to Improve Problem Solving Ability - Setiyadi, Desi; Zaenuri, Zaenuri; Mulyono, Mulyono (Journal of Primary Education, 2018)
The purpose of this study was to determine the effectiveness of the Problem Based Learning (PBL) model with etnomatematics nuance by using traditional games to improve students problem solving ability. The population in this study was the fourth grade students of SDN Mandirancan, Kebasen, Banyumas Academic Year 2017/2018. Sampling was done by using simple random sampling. Data collection technique applied was problem solving ability tests, observation and documentation. This study was analyzed by using t-test. The results show that (1) the ability of problem solving using PBL models with etnomatematics nuanced by using traditional games has reached the classical completeness 75%, (2) the average scores of problem solving ability by using the model of PBL with etnomatematics nuanced by using traditional games was better than the average scores of problem solving ability by using the model of expository, (3) the average gap of problem solving ability by using the model of PBL with etnomatematics nuanced by using traditional games was better than the average gap of problem solving ability by using expository model. Based on the above results, it can be concluded that the model problem based learning with etnomatematics nuanced by using traditional games is effective in improving students' problem solving ability.